High‐ versus low‐intensity internet interventions for alcohol use disorders: results of a three‐armed randomized controlled superiority trial. (3rd January 2020) - Sundström, Christopher; Eék, Niels; Kraepelien, Martin; Fahlke, Claudia; Gajecki, Mikael; Jakobson, Miriam; Beckman, Maria; Kaldo, Viktor; Berman, Anne H.
Abstract: Aims: To test the efficacy of a therapist‐guided high‐intensity internet intervention compared with an unguided low‐intensity internet intervention among individuals with alcohol use disorder. Design: A three‐group randomized controlled trial with follow‐up assessments post‐treatment (12 weeks) and 6 months post‐randomization (primary end‐point). Settings: General population sample in Sweden. Participants: A total of 166 on‐line self‐referred adults (49% males) with a score of 14 (females)/16 (males) or more on the Alcohol Use Disorders Identification Test, a preceding week alcohol consumption of 11 (females)/14 (males) or more standard drinks and an alcohol use disorder according to a diagnostic interview. Interventions and comparators: Both the high‐ ( n = 72) and low‐intensity internet interventions ( n = 71) consisted of modules based on relapse prevention. Controls were on a waiting‐list ( n = 23), and were only followed until the post‐treatment follow‐up. Participants were randomized at a 7 : 7 : 2 ratio. Measurements: Primary outcome was self‐reported alcohol consumption in the preceding week measured as (1) number of standard drinks and (2) number of heavy drinking days at the 6‐month follow‐up. Findings: Alcohol use disorders were largely in the severe category (74.7%), with the majority of participants having had alcohol problems for more than 5 years. Attrition was 13 and 22% at the post‐treatment and 6‐month follow‐up, respectively. At the 6‐month follow‐up, an intent‐to‐treat analysis showed no significant differences in alcohol consumption between the high‐ and low‐intensity interventions [standard drinks d = −0.17, 95% confidence interval (CI) = −0.50 to 0.16; heavy drinking days: d = −0.07, 95% CI = −0.40 to 0.26]. Prevalence of negative effects was somewhat low (8–14%) in both intervention groups, as was deterioration (3–5%). Conclusions: At 6‐month follow‐up, there were no significant differences between a therapist‐guided high‐intensity internet intervention and an unguided low‐intensity internet intervention in reducing alcohol consumption among individuals with an alcohol use disorder.